Determinación de los cambios en la humedad y color en ñame criollo (dioscorea alata) durante el secado por ventana refractiva (2020)
The aim of this work was to determine the influence of drying temperature on humidity and color in “criollo” yam (Dioscorea alata) by the refractive window technique. The “criollo” yams were selected from the public market of the municipality of Ciénaga de Oro (Córdoba) according to their variety, size, weight, uniform thickness, absence of physical and biological damage. Then the yam was washed, disinfected, rinsed and peeled. A completely randomized design was used with three levels of the Temperature factor: {70, 80, 90} °C and three replications. The samples were suitable in the form of sheets with dimensions of 3.5 cm long x 3.5 cm wide and 3.5 mm thick. The samples were placed to dry in a refractive window dryer at a drying temperature of 70, 80 and 90 °C. The color was measured using the Color Flex EZ colorimeter and the humidity was measured by the oven method at 105°C; subsequently, the color change (ΔE*) was calculated, the effective moisture diffusivity was determined using the mathematical model of Fick's second law and the activation energy was estimated using the Arrhenius model. It was found that in the refractive window drying, the temperatures had a significant difference (p<0.05) on the humidity, the effective diffusivity observing that as the temperature increases, also increases the humidity loss, while for the parameters L *, a *, b * and ΔE * the values were not significantly different (p <0.05). The effective diffusivity of had values between 2.83x10-8 and 6.05x10-8 m2 /s, the activation energy (Ea) was 39.6 kJ/mol. Finally, it was observed that refractive window drying preserves the color compared to hot air drying